Transforming The Bad Debt Into Cash Flow - Palaniandy, Magendran Pillai (2010)
The increasing amount of bad debt and uncollected accounts in the banks and other creditors have affected the cash inflow very badly. The transformation of bad debt into cash flow is vey crucial for daily business operation or for further expansion in the future. In view of the above, effective collection and recovery of bad debt strategies are very important for the business to be successful and mitigate losses. Banks and creditors maintain the current recovery model, the in-house collection activities to recover the bad debt. However, in certain circumstances, the amount recovered is not as expected and as such, alternative options are required. The two most feasible and efficient recovery tools are to outsource the bad debt to an established debt collection agency or to sell the bad debt to an interested buyer to maximize the recovery. The procedures, concepts, and workflow including the guidelines of Bank Negara Malaysia involved in all the three options are outlined to have a better understanding and comparison on the different recovery activities. Literature reviews on the causes of bad debt and other recovery tools are discussed with the relevant examples. These bad debt problems are not only affecting Malaysia, but also has been a major problem in the developed and emerging economies. The worldwide financial crisis has affected a lot of banks and other creditors with substantial amount of bad debt. Further, the increasing demand for unsecured loans including credit cards is one of the main causes for increasing of bad debt amount. The research is conducted with the appropriate research methodology and suitable respondents are selected as the samples. The feedbacks from the interview are reported and summarized in a tabular format to develop three different hypotheses. The findings are discussed in detail with the benefits and limitations available for the three alternatives. The selection of the recovery tool is subject to the guidelines and requirement of the individual bank or creditor to maximize recovery and minimize the cost of operation.